MAKNA ELEMEN PENDUKUNG INTERIOR PADA ARSITEKTUR RUMAH IBADAH - Krismanto, Robertus; Soesilo, Rudyanto; Susanti, Bernadeta Tyas (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2020)
The architecture and interior of the Church of the Sacred Heart of the Lord Jesus Ganjuran (HKTY) Bantul Yogyakarta in the form of joglo with supporting elements in the form of interior furniture, statues, decoration, domes, glass paintings. This study uses a qualitative method with a case study at the Church of HKTY Ganjuran research focus on finding the meaning of interior supporting elements. Retrieval of data through interviews, observation, documentation, and literature study. The results of the study that the supporting elements of the interior have meaning to support people praying or worshiping. On some furniture there are ornaments about pelicans that have the meaning of the Sacred Heart, the Most Holy, who is willing to give life, for his children to stay alive. Sculptures in Javanese outfit so that people near are easy to pray with God because they come with Javanese faces. The decoration on the dome above the priest's sanctuary contained symbol images of the four gospels and The Most Holy Trinity. That is, when the Imam consecrated and looked up always always permeated the four holy Gospels and The Most Holy Trinity. This kind Samaritan glass painting is located on the east side of the Ganjuran church priest's home so that Catholics after attending the Eucharist are ready to do for anyone in need, because faith without works is dead. The colors used are green which means fertility, growth and indicates hope. The yellow color of gold means the glory of God, the red color means martyrdom, sacrifice and black has a meaning of origin and harmony. The people when praying are increasingly directed towards God because they are helped by the architecture and interior of the church which is a condition for meaning.Keywords: HKTY Ganjuran Church; interior supporting elements. ABSTRAK Arsitektur dan interior Gereja Hati Kudus Tuhan Yesus Ganjuran (HKTY) Bantul Yogyakarta berupa joglo dengan elemen pendukung interior berupa furnitur, patung -patung, ragam hias, kubah, lukisan kaca. Penelitian ini menggunakan metode kualitatif dengan studi kasus pada Gereja HKTY Ganjuran fokus penelitian pada menemukan makna elemen pendukung interior. Pengambilan data melalui wawancara, observasi, dokumentasi, dan studi pustaka. Hasil penelitian bahwa elemen pendukung interior mempunyai makna untuk mendukung umat berdoa atau beribadat. Pada beberapa perabot terdapat ornamen tentang burung pelikan yang mempunyai makna Hati KudusYang Maha Kudus, yang bersedia memberikan hidup, bagi anak-anaknya agar tetap hidup. Patung - patung dengan busana Jawa agar umat dekat mudah untuk berdoa dengan Tuhan karena hadir dengan wajah Jawa. Ragam hias pada kubah yang berada di atas panti imam ini terdapat gambar simbol ke empat Injil dan Tritunggal Maha Kudus. Maksudnya ketika Imam melakukan konsekrasi dan menengadah keatas selalu meresapi tentang ke empat Injil suci dan Tritunggal Maha Kudus. Lukisan kaca orang Samaria yang baik hati ini terletak di sisi timur panti imam gereja Ganjuran agar umat Katolik seusai mengikuti perayaan ekaristi siap sedia berbuat bagi siapapun yang membutuhkan, sebab iman tanpa perbuatan adalah mati. Warna – warna yang dipergunakan yaitu warna hijau mempunyai makna kesuburan, pertumbuhan dan menandakan pengharapan. Warna kuning emas bermakna kemuliaan Allah, warna merah menunjukkan kemartiran, pengorbanan dan warna hitam mepunyai makna asal mula dan kesejatihan. Umat ketika berdoa semakin terarah kepada Tuhan karena terbantu oleh arsitektur dan interior gereja yang syarat akan makna.